The combustion of titanium powder in air and iron oxide - Brown, Robert Alexander (2000)
The quest for ever stronger and tougher steels has lead to an interest in the 'Acicular Ferrite' microstructure, its chaotic and disordered morphology imparting a high degree of toughness to the steel. To date, only complex and expensive materials and manufacturing processes have formed acicular ferrite within bulk cast steel. As such, the thrust of this research is to produce a cheap steel addition, an iron - titanium oxide metal-ceramic composite, that will facilitate the formation of acicular ferrite in conventionally manufactured bulk cast steels.